AGRICULTURE IN URBAN ECOSYSTEMS: A STEP TO CITIES SUSTAINABILITY1 - BATITUCCI,THAYZA DE OLIVEIRA (2019)
Abstract Urban Agriculture (UA) has emerged as an alternative capable of fostering sustainable relations among the economic, social and environmental spheres in cities. It consists of growing and processing traditionally rural food products in urban zones in consonance with the environmental considerations to promote sustainability. This study set out to analyze the interactions of agricultural activities and the urban ecosystem. A review of the literature and a case study of an Urban Agriculture program developed in the metropolitan area of the city of Rio de Janeiro showed that Urban Agriculture provides considerable ecosystem services, generates income, increases biodiversity conservation and fosters social inclusion, functioning as a mechanism for achieving equilibrium among the components of the urban ecosystem.